Technology, technology, technology: An integrated assessment of deep decarbonization pathways for the Canadian oil sands. (May 2022) - Bergero, Candelaria; Binsted, Matthew; Younis, Osama; Davies, Evan G.R.; Siddiqui, Muhammad-Shahid; Xing, Rui; Arbuckle, Evan J.; Chiappori, Diego V.; Fuhrman, Jay; McJeon, Haewon; Macaluso, Nick
Abstract: As a party to the Paris Agreement, Canada has an ambitious climate target of net-zero emissions by 2050. The country also holds the world's third largest oil reserves in the Alberta oil sands. Given increasing emissions from the oil sands sector, achieving Canada's net-zero target requires significant oil sands decarbonization. If, while phasing out fossil fuels, there is still a demand for Canadian oil sands, then the decarbonization of the resource production process becomes crucial. In this study, we use an enhanced version of the Global Change Analysis Model (GCAM) with a detailed unconventional oil sector for Canada, including mining and in situ resources. We ask, what is the future of the oil sands sector in deeply decarbonized global and Canadian economies? We address this question under four mitigation scenarios with varying global net-zero GHG emissions constraints, three additional representative lower carbon extraction technologies available for the oil sands sector, as well as global direct air capture (DAC) deployment. We find that lower carbon technology deployment allows a 20% – 44% increase in oil sands production by 2050 for scenarios with net-zero GHG emissions in 2100 or 2075. DAC helps maintain oil sands production in the most ambitious global decarbonization scenario (net-zero GHG by 2050), without which low international oil demand makes Canadian oil sands production uncompetitive. Canadian oil sands production thus depends highly on the availability of lower carbon extraction technologies and international oil demand, which to a certain extent relies on the availability and global deployment of negative emissions technologies. Highlights: Technology is crucial for Canadian oil sands development in deep decarbonization scenarios. Lower carbon extraction technologies can help decarbonize the oil sands sector. DAC allows for a higher global oil demand and thus higher oil sands production.